Electropolymerization of chitosan in the presence of CuNPs on the surface of a copper electrode: an advanced nanocomposite for the determination of mefenamic acid and indomethacin in human plasma samples and prevention of drug poisoning. Issue 9 (19th February 2020) - Farshchi, Fatemeh; Hasanzadeh, Mohammad; Feyziazar, Mahsa; Saadati, Arezoo; Hassanpour, Soodabeh
Abstract : An innovative method was introduced for the electro-polymerization of chitosan on the surface of a copper electrode. Abstract : An innovative method was introduced for the electro-polymerization of chitosan on the surface of a copper electrode. Two electrochemical sensors for the detection and determination of indomethacin and mefenamic acid in human plasma samples were constructed based on copper nanoparticles (CuNPs) and poly-chitosan-modified CuNPs, respectively. The electrochemical behaviors of the CuNP-modified copper electrode (CuE) and poly-chitosan-doped CuNP-modified copper electrode (P(CS)-CuNP-CuE) were investigated using differential pulse voltammetry and cyclic voltammetry techniques. The electrochemical results show that CuNPs and P(CS)-CuNPs lead to increased oxidation peak current by the adsorption of indomethacin. According to the obtained results, we inferred that the linear range and low limit of quantification (LLOQ) were 1 nM to 10 mM and 1 nM, respectively.